Revisiting The Current Environmental Status Of The Marikina River, Philippines - Crispino, Marwin; Clemente, Eligia (Jurnal Teknik Lingkungan, 2025)
Abstract: The physico-chemical characteristics of the Marikina River in an urban area of Metro Manila, Philippines was determined to evaluate the current degree of pollution. The study focused on one source at the site with general coordinates of 14°38'07.95" N, 121°05'36.33" E based on the World Geodetic System (WGS), at an average surface water elevation of around 9 m above mean sea level (AMSL). The area was chosen because of its proximity to a main road and the presence of an outfall from a cemented pipe near a major shopping mall. Comparing the results from the sampling source with the DENR effluent standards for surface waters based on (DAO-2016-08, US-EPA), the effluent is considered as too polluted to be discharged to the surface water in terms of Total Dissolved Solids (TDS: 608.9 mg/L) and Phosphates (PO4: 12.46 mg/L). The pH (6.9) and Nitrate (0.17 mg/L) of the effluent conforms to standards. A Stream Visual Assessment Protocol was conducted with a resulting Protocol Score of 5.7, which is relatively low for a moving water body. The failure to conform to set standards using the physico-chemical components is supported by the land-use profile which shows that domestic (85%), industrial/commercial (10%) and agricultural wastes (5%) greatly affect the water quality of the river. It is our recommendation therefore that continuing information and education campaigns for the maintenance of water quality be regularly conducted for the residents along the riverbanks to create awareness of the importance of keeping the water clean through minimum direct waste contributions.